2013
DOI: 10.1021/ma400661f
|View full text |Cite
|
Sign up to set email alerts
|

Dicyano-Substituted Poly(phenylenevinylene) (DiCN–PPV) and the Effect of Cyano Substitution on Photochemical Stability

Abstract: A didecyloxy-substituted poly(phenylenedicyanovinylene), DiCN–PPV, has been synthesized. The dicyano-substituted vinylene units exist in both trans and cis (∼65:35) conformations as determined by 1H NMR analysis, and cannot be converted to all trans due to the presence of a thermodynamic equilibrium of the two conformations, in contrast to the vinylene units in regular PPVs. The unusually high cis content makes this polymer highly amorphous, very soluble in organic solvent, and highly fluorescent in the solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…This behavior was generally already observed in previous research upon polymerizing CN-PPV as homopolymer. 40 In addition, a comparison of the molecular weights and its accompanying dispersities between GPC and MALLS measurements, indicates the over estimation of the GPC, as dispersities obtained via MALLS measurements all show values below 1.5, underpinning the living behavior of PPV monomers via the anionic sulfinyl route using dedicated anionic initiators. 31 Further UV-Vis and fluorescent results indicate the considerable influence of the inclusion of the CN pre-monomer, see Figure 4.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…This behavior was generally already observed in previous research upon polymerizing CN-PPV as homopolymer. 40 In addition, a comparison of the molecular weights and its accompanying dispersities between GPC and MALLS measurements, indicates the over estimation of the GPC, as dispersities obtained via MALLS measurements all show values below 1.5, underpinning the living behavior of PPV monomers via the anionic sulfinyl route using dedicated anionic initiators. 31 Further UV-Vis and fluorescent results indicate the considerable influence of the inclusion of the CN pre-monomer, see Figure 4.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Unsubstituted PPV has a bandgap of about 2.4 eV, which is reduced to 2.2 eV with the introduction of electron‐donor alkoxy groups on the benzene ring . The insertion of a nitrile group on the ethene bridge lowers both the LUMO and HOMO levels by ≈0.5 eV, with a little effect on the magnitude of the band gap, and increases the stability of the polymer with respect to photo‐oxidation, which is one of the main weak points of this family of materials. Other research groups have worked on alkyl substituted donor–acceptor copolymers with a bis (1‐cyano‐2‐thienylvinylene)phenylene base structure that showed band gaps of 1.7–2.4 eV.…”
Section: Introductionmentioning
confidence: 99%
“…This holds true with respect to the polymers that are known to degrade by a radical mechanism. Poly[2,5‐bis(decyloxy)−1,4‐phenylenevinylene] (RO‐PPV) with a LUMO level of −2.91 eV degrades faster than poly[2,5‐bis(decyloxy)cyanoterephthalylidene] (CN‐PPV) with a LUMO level of −3.29 eV . To increase the stability of PPV‐type polymers we synthesized a poly[2,5‐bis(decyloxy)−1,4‐phenylene‐1,2‐dicyanovinylene] (RO‐diCN‐PPV), the dicyano substituents on the vinylene unit lowered the LUMO level from −2.91 eV for RO‐PPV to −3.54 eV.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that singlet O 2 is responsible for the higher rate of photodegradation observed for C8‐diCN‐PPV due to intersystem crossing to its triplet state. Formation of an imide linkage, a side reaction of dicyanovinylene formation, which was unnoted in the previously reported synthesis of RO‐diCN‐PPV and C8‐diCN‐PPV was identified, and the synthesis of these polymers was modified to avoid this structural defect from the side reaction.…”
Section: Introductionmentioning
confidence: 99%